MANDIBULR CONDYLE FRACTURE MANAGEMENT OUTCOME IN DEPARTMENT OF PLASTIC RECONSTRUCTIVE AND AESTHETIC SURGERY, DR. SOETOMO GENERAL ACADEMIC HOSPITAL (2015-2018) - Lobredia Zarasade; Iswinarno Doso Saputro; Nadia Tamara Putri (Jurnal Rekonstruksi dan Estetik, 2020)
Highlights: